2c+3=4(5c-6)

Simple and best practice solution for 2c+3=4(5c-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2c+3=4(5c-6) equation:


Simplifying
2c + 3 = 4(5c + -6)

Reorder the terms:
3 + 2c = 4(5c + -6)

Reorder the terms:
3 + 2c = 4(-6 + 5c)
3 + 2c = (-6 * 4 + 5c * 4)
3 + 2c = (-24 + 20c)

Solving
3 + 2c = -24 + 20c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-20c' to each side of the equation.
3 + 2c + -20c = -24 + 20c + -20c

Combine like terms: 2c + -20c = -18c
3 + -18c = -24 + 20c + -20c

Combine like terms: 20c + -20c = 0
3 + -18c = -24 + 0
3 + -18c = -24

Add '-3' to each side of the equation.
3 + -3 + -18c = -24 + -3

Combine like terms: 3 + -3 = 0
0 + -18c = -24 + -3
-18c = -24 + -3

Combine like terms: -24 + -3 = -27
-18c = -27

Divide each side by '-18'.
c = 1.5

Simplifying
c = 1.5

See similar equations:

| 4(2x+3)+5=1 | | -5x-4(-7-4x)=36+7x | | 60=4(5-x) | | 2(5+x)=-30 | | x-21=-x*2 | | 3(7x-7)=-6+6x | | 4x-148=3x+566 | | 50+0.9*(y-30)+10+10+28=y | | 5[2-3(x-8)]=26-8x | | (2x^4)+16x=0 | | 2x+(-4x)=22 | | 4x+9-49=0 | | -1+3(v-7)=-28 | | 2x^2+22x+60=x | | 20y+13=15y-8 | | 4x+4x=64 | | (18a^3)-72a=0 | | z-0.45=5.97 | | 3a+(4b+2)I=9-6I | | 50+0.9*(y-30)=y | | -5x+24=-8(x-6)+6x | | -(-a)= | | 3x(4)=2 | | -n+n= | | 2(4z-2)-2(5-3z)=4 | | 5x+5=4x+4 | | 11+2(3n-11)=1 | | 6((2n^2)+3n-35)=0 | | (3x+4)-30=0 | | t-45=-48 | | 4x+8y-3x+2y= | | 1x+2y=18 |

Equations solver categories